Surabaya Tourism Destination Recommendation Using Fuzzy C-Means Algorithm - Sutjiadi, Raymond; Trianto, Edwin Meinardi; Budihardjo, Adriel Giovani (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Determining tourism destination requires various criteria that suitable for the travelers’ needs. Usually, travelers explore tourism destination through the internet or have recommendation from their relatives. That way is not informative because most people will recommend well-known tourism destination based on their experience only. In this research, C-Means Fuzzy Clustering is used to build a decision support system in selecting tourism destination in Surabaya, Indonesia. By using this application, the travelers, who want to visit Surabaya city, is not only provided the information related to tourism destination, but also nearest hotel and restaurant that suitable to traveler’s criteria and budget. This application processes the input into the desired output in the form of recommendation based on the calculation of the degree of membership and center of the cluster.